HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKANWANITA PEKERJA SEKSUAL TIDAK LANGSUNG TENTANG PAP SMEAR DAN INSPEKSI VISUAL ASETAT PADA SEBAGAI DETEKSI DINI KANKER SERVIKS DI HOTSPOT X KECAMATAN LIMA PULUH PEKANBARU - Rifqi Rahmadhan; Wiwit Ade Fidiawati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignancythat originatesfrom cervical cell. Cervicalcancer is ranked as second most common cancer in Indonesia. Indirect female sexworker (FSW) has high risk getting cervical cancer. The aim of this study is tofindcorrelation between knowledge and attitude towards practice of indirectFSWabout Pap smear and VIA as an early detection of cervical cancer at hotspotX District Lima Puluh Pekanbaru. The method of this research is analytic crosssectional. Population is indirect FSW living in the hotspot X and samples weretaken with total sampling method to 31 people through interviews usingquestionnaire. The results showed that among 31 FSWs, 17 people (54.8%) are26-35 years old, 12 people (38.7%) areSenior High School (SHS) graduate, 14people (45.2%) have poor knowledge, 18 people (58.1%) have a positive attitudeand 26 people (83.9%) do this test. There is no correlation between knowledgeand attitude (p=0.304), no correlation between knowledge and practice(p=0.085).But there is a correlation between attitude and behaviour (p=0.003). Itis concluded that the majority of indirect FSW at hotspot X Lima Puluh districthave bad knowledge, positive attitude andwilling to do Pap smear and VIA as anearly detection of cervical cancer.Keywords: Knowledge, Attitude, Practice,Indirect Female Sex Worker